Tri-primer-enhanced strand exchange amplification combined with rapid lateral flow fluorescence immunoassay to detect SARS-CoV-2. Issue 21 (5th October 2021) - Zhuang, Linlin; Gong, Jiansen; Ma, Ming; Ji, Yongxin; Tian, Peilong; Mei, Xiuming; Gu, Ning; Zhang, Yu
Abstract : A novel, rapid and sensitive lateral flow fluorescence immunoassay combined with tri-primer-enhanced strand exchange amplification (ESEA-LFIA) for the quantitative detection of SARS-CoV-2 was developed. Abstract : The novel coronavirus disease 2019 caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been surging rapidly around the world, which has exposed humanity to unprecedented economic, social and health impacts. To achieve efficient and accurate detection of SARS-CoV-2 on site, we developed and verified a rapid and sensitive fluorescence lateral flow immunoassay based on the innovative enhanced strand exchange amplification (ESEA-LFIA) in this study. With good amplification efficiency for short-sequence targets, ESEA is an ideal choice for the point-of-care testing of SARS-CoV-2 with a high mutation rate. ESEA reaction can be completed in one step and verified by restriction enzyme digestion. The design consisting of three working primers greatly improved the amplification efficiency. Amplification of the target sequences of the RdRP and N genes can be accomplished under the same reaction conditions, and does not require expensive instruments. The sensitivity of the ESEA-LFIA assay targeting the RdRP and N genes was 90 copies per μL and 70 copies per μL, respectively. Specificity tests showed that the novel assay can specifically detect SARS-CoV-2, and had no cross-reactivity with 9 closely-related human pathogenic coronaviruses and other common respiratory pathogens with similar clinical manifestations. The cutoff values of the RdRP and N gene assays are 11 and 12, respectively, and the assays can be completed within 1 h. The novel strategy proposed in this study is a sensitive and specific method for the rapid detection of SARS-CoV-2, and is suitable as an effective potential bioanalytical tool to respond to future regional or global outbreaks of emerging infectious pathogens with high mutation rates.